Impact of Intended Mode of Delivery on Outcomes in Preterm Growth-Restricted Fetuses - Baalbaki, Sima H.; Kuper, Spencer G.; Wang, Michelle J.; Steele, Robin A.; Biggio, Joseph R.; Harper, Lorie M. (American Journal of Perinatology, 2018)
Background Scheduled cesarean is frequently performed for fetal growth restriction due to concerns for fetal intolerance of labor.Objective We compared neonatal outcomes in preterm growth-restricted fetuses by intended mode of delivery.Study Design We performed a retrospective cohort study of indicated preterm births with prenatally diagnosed growth restriction from 2011 to 2014 at a single institution. Patients were classified by intended mode of delivery. The primary outcome was a composite of adverse neonatal outcomes, including perinatal death, cord blood acidemia, chest compressions during neonatal resuscitation, seizures, culture-proven sepsis, necrotizing enterocolitis, and grade III–IV intraventricular hemorrhage. Secondary analysis was performed examining the impact of umbilical artery Dopplers.Results Of 101 fetuses with growth restriction, 75 underwent planned cesarean deliveries. Of those induced, 46.2% delivered vaginally. Delivery by scheduled cesarean was not associated with a decreased risk of the composite outcome (adjusted odds ratio [aOR], 1.61; 95% confidence interval [CI], 0.45–5.78), even when only those with abnormal umbilical artery Dopplers were considered (aOR, 2.8; 95% CI, 0.40–20.2).Conclusion In this cohort, planned cesarean was not associated with a reduction in neonatal morbidity, even when considering only those with abnormal umbilical artery Dopplers. In otherwise appropriate candidates for vaginal delivery, fetal growth restriction should not be considered a contraindication to trial of labor.
Keywords: intrauterine growth restriction; preterm delivery; mode of delivery; umbilical artery Dopplers